The System Analysis of Ensuring the Stability of Innovative and Digital Economy on the Basis of Intellectual Comprehensive Security System - Ogorodnikov, Petr Ivanovich; Zaloznaya, Galina Mikhaylovna; Borovsky, Aleksandr Sergeevich (Economy of Regions, 2018)
The article is based on the system approach and the analysis of ensuring economic security as well as on the developed conceptual techniques devoted to the security of regional enterprises. We consider the issues of the interaction of subsystems of the general system of national security in regions. The purpose of the study is to develop a comprehensive methodology for the assessment of the national security in regions including all main directions: economy, ecology, information, etc. Currently, the need for a theory of security of regional enterprises has, first of all, an applied nature. At the same time, without basic fundamental knowledge of the theory of comprehensive security, it is impossible to provide sustainable development of regional enterprises. We conduct a comprehensive research of all types of security on the basis of the system approach and the analysis. Furthermore, we move from task-specific study to the system research of the examined objects and systems. It has allowed analysing the internal interrelations of subsystems including the subsystems of economic security in the framework of the general system of national security. We propose the method, which substantiates the quality of enterprise security using the fuzzy set method and fuzzy multi-criteria method in relation to the paper’s topic. Moreover, we apply the Bellman and Zadeh’s principle allowing to choose an option, which satisfies all criteria in the maximum degree. The developed approach to the formation of a comprehensive assessment of all types of security will allow providing sufficient explanations to the influence and interaction of subsystems within the national security’s general system as well as will significantly increase the economic stability of regional enterprises and organizations.